Study of Coconut Cake Utilization for Bioethanol Production with Solid Fermentation by Mix Culture (Aspergillus niger, Trichoderma reesei,& Saccharomyces cerevisiae) - Husnul Chotimah, Nuni
Nowadays, bioethanol has become an alternative fuel to solve the limitation of fossil fuel and has potency in reducing air pollution. Biomass containing sugar, starch, or cellulose can be used as bioethanol raw material. Coconut cake is byproduct of coconut oil processing which contains carbohydrate and fiber, so it can be used as substrate to produce bioethanol. The research to use coconut cake as bioethanol raw material through solid fermentation with mix culture (Aspergillus niger, Trichoderma reesei, and Saccharomyces cerevisiae) has been conducted. This research was conducted through steps which were coconut cake and rice bran composition optimization, substrate hydrolysis by mix culture and single culture, and the optimization of fermentation condition. From step one, the result showed that mix culture of Aspergillus niger and Trichoderma reesei (1:1) with substrate containing 80% of coconut cake and 20% of rice bran could significantly (p<0,05) produce higher reducing-sugar (on day 2 and day 5) compared with 100% of coconut cake substrate. On step two, the result showed that the hydrolysis substrate (80% of coconut cake and 20% of rice bran) with mix culture of Aspergillus niger and Trichoderma reesei (1:1) could produce higher reducing-sugar on day 3, but this result was not significantly different (p<0,05) with single culture of Aspergillus niger and Trichoderma reesei. On day 3 of substrate hydrolysis, the activity of CMCase and glucoamylase was increased in mix and single cultures. On the last step, ethanol fermentation with various iv condition shows that the higher ethanol concentration was produced in medium with 80% coconut cake and 20% rice bran substrate (10 grams of substrate weight, 66,7% of initial humidity, and 5,3 of initial pH) which was inoculated with Aspergillus niger and Trichoderma reesei (1:1) on day 0 and incubated in Erlenmeyer covered with cotton, and later inoculated with Saccharomyces cerevisiae on day 3 and kept in Erlenmeyer covered with rubber seal. The highest ethanol concentration (32,5 mg/g substrate or 3,25% (w/v) was produced under the above conditions was reached at day 6 of culture period. Based on the result, it can be concluded that coconut cake substrate could produced ethanol through solid fermentation with mix culture of Aspergillus niger, Trichoderma reesei, and Saccharomyces cerevisiae.